Annual Plan Proposals 1986-87 Government of Kerala - Planning Commission (Planning Commission, 1986)
A well developed and fairly well distributed network of public utilities and social services exists in Kerala due to the emphasis given to communications, education and health facilities and other social welfare measures during the previous plans. Unless some of the productive economic sectors such as industry, trade and commerce grow fast enough to absorb the skilled and semi-skilled manpower making use of the existing infrastructure facilities the social investments made in the past will continue to give uneconomic returns.
State Planning Board, Trivandrum